Are Men Making Informed Decisions According to the Prostate-Specific Antigen Test Guidelines? Analysis of the 2015 Behavioral Risk Factor Surveillance System - Cooper, Dexter L. (Am J Mens Health, 2019)
The prostate-specific antigen (PSA) screening recommendation endorses the opportunity for men to make an informed decision about whether or not to screen. This entails speaking with a provider to discuss the potential advantages, disadvantages, and uncertainties about the PSA screening test. The purpose of this study was to examine (a) the reported level of being informed about the PSA test by race and (b) the association between the receipt of the PSA test and participants reporting that they were informed about the test. U.S. adult males (ages 40–74 years) were identified from the 2015 Behavioral Risk Factors Surveillance System (BRFSS; n = 3,877). Chi-square analysis assessed bivariate differences among men who received different levels of PSA screening information. Binomial logistic regression models assessed the relationship of race/ethnicity and the receipt of the PSA test on being informed about the PSA test. Over half (54.3%) of the sample had a PSA test and most (72.0%) reported that they did not receive information about both the advantages and disadvantages (being informed) of the PSA test. Black men (40.3%) were significantly most likely to report being informed (p < .001), and 61.3% reported receipt of a recommendation from their provider (p < .001). White men (63.1%) were significantly more likely to report receiving the PSA test. Findings indicate that more men reported receiving the PSA test than men who reported being informed about it. Future research and interventions should strive for men of all racial and ethnic backgrounds to be informed about the PSA test before making a decision.